The Practice of Expropriation through Related Party Transactions In Indonesia - Malinda Kharista; Bambang Purnomosidhi; Imam Subekti (Universitas Muhammadiyah Malang, 2020)
The purpose of this study to examine the influence of governance toward an expropriation practice in Indonesia and to examine the institutional ownership that acts as a moderator in strengthening the effect of corporate governance toward an expropriation practices as measured by related party transactions. This study uses panel data regression analysis. The results showed that corporate governance negatively affects the practice of expropriation and institutional ownership cannot strengthen the influence of corporate governance toward an expropriation practice. This research contributes to the type II agency theory (conflicts between controlling and non-controlling shareholders), which can be minimized by implementing corporate governance.